Boko Haram Insurgency and Violation of Children’s Rights in North East, Nigeria - Adebajo, Adeola Aderayo; Salako, Samuel Anuoluwapo; Goodness, Rotimi; Akinsola, Alameen Abolade (Department of Political Sciences, Faculty of Social and Political Sciences, UIN Sunan Ampel Surabaya, 2025)
Boko Haram insurgency in the North East Nigeria has posed significant challenges to the protection of children's rights. Adopting the child right- based theory, the paper investigated how Boko Haram insurgency violated children’s rights in the region. Desk research method which relied on secondary sources was employed. It argued that insurgency by Boko Haram sect violated children’s rights in the region in form of recruitment of child soldiers, sexual violence, abduction, denial of access to education and healthcare. The paper discusses the causes of the conflict, including poverty, marginalization, lack of access to education and economic opportunities, as well as their implications for children's rights. The paper also assesses the response of the Nigerian government and the international community to the crisis, including military operations against Boko Haram, efforts to rehabilitate and reintegrate former child soldiers, and initiatives to promote peace, reconciliation, and development in the region. While acknowledging some progress in addressing the crisis, the paper highlights ongoing challenges, including the need for greater protection of children's rights, increased access to education and healthcare, and addressing the root causes of the conflict. It recommended protection mechanisms, promoting peace and reconciliation, and addressing the underlying factors driving insurgency in order to ensure the realization of children's rights in the region